Poseidon's warriors classical naval warfare 480-31 BC - Lambshead, John (Osprey wargames, 2015)
With data for ships throughout the period, rules for famous admirals, historical scenarios, a campaign system and a brief historical summary for those who wish to refresh their memory of the era, this title offers everything players need to bring to the tabletop the battles and campaigns of the first great age of naval warfare.